Menyelidiki kesulitan siswa SMP dalam menjawab soal kemampuan pemecahan masalah matematis ditinjau dari level kemampuan siswa - Jamilah, Siti Marwah; Sugandi, Asep Ikin; Pertiwi, Citra Megiana (IKIP Siliwangi, 2023)
The purpose of this research was to identify students' difficulties in answering questions about mathematical problem solving abilities (KPMM) on the material quadratic equation (PK). The method used in this research is qualitative descriptive method. The subjects in this research were 18 students of class IX at SMPN 1 Cihampelas. The data collection technique was using a test question the KPMM with of 4 grains question. The results of this research found the level of students' ability to answer KPMM-PK questions based on the KPMM steps. The highest percentage of 74% lies in the difficulty of checking the correctness of answers with difficult criteria. While the lowest percentage of 60% lies in the difficulty of planning a settlement with quite difficult criteria. Meanwhile, when viewed from the level of student ability, the difficulties of students with high abilities have not difficult criteria, the difficulties of students who have moderate abilities are in the slightly difficult criteria, and the difficulties of students who have low abilities lie in quite difficult criteria.